2013
DOI: 10.1016/j.rvsc.2013.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Virulent feline calicivirus disease in a shelter in italy: A case description

Abstract: Feline calicivirus (FCV) is a common pathogen of cats that is particularly widespread in multi-cat environments such as shelters and catteries. FCV infections are usually associated with acute, mild and self-limiting upper respiratory tract disease characterized by oral vesicles/ulcers. Recently, virulent systemic disease (VSD) associated with FCV infection has been reported in the USA and Europe. This paper describes a case of VSD affecting one adult, FIV infected cat ("Oscar") living in a shelter located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 28 publications
1
54
0
2
Order By: Relevance
“…It is noteworthy that asymptomatic cats can represent an important source of infection (BATTILANI et al, 2013;MÖSTL et al, 2013), so constant surveillance including molecular testing for FHV-1 may be important for the sanity of those animals. The animals in the present study were housed together regardless of whether they were showing clinical signs or not.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that asymptomatic cats can represent an important source of infection (BATTILANI et al, 2013;MÖSTL et al, 2013), so constant surveillance including molecular testing for FHV-1 may be important for the sanity of those animals. The animals in the present study were housed together regardless of whether they were showing clinical signs or not.…”
Section: Discussionmentioning
confidence: 99%
“…Group 4 comprised four cats with VS-FCV; pulmonary specimens from these cats were examined by IH for the presence and distribution of FCV. Most of the cats in group 4 have since been reported as confirmed cases of VS-FCV in the UK (Coyne et al, 2006a), Italy (Battilani et al, 2013) and Spain (Velasco et al, 2013).…”
Section: Animals and Tissuesmentioning
confidence: 99%
“…Moreover, in 1998, new highly virulent VS-FCV strains emerged. The first VS-FCV cases were observed in California (Pedersen et al, 2000), but further outbreaks have subsequently been reported from the USA (Schorr-Evans et al, 2003;Hurley et al, 2004;Pesavento et al, 2004) and, more recently, Europe (Coyne et al, 2006a;Schulz et al, 2011;Battilani et al, 2013;Velasco et al, 2013). The most frequent clinical signs are cutaneous oedema (mainly on the head and limbs), ulceration of the skin and mucosa, predominantly affecting the oral cavity, nares, pinnae and footpads, and clinical signs due to multi-organ necrosis, most commonly affecting the liver, but occasionally also the spleen, pancreas or lungs (Pedersen et al, 2000;Hurley and Sykes, 2003;Coyne et al, 2006a;Radford et al, 2007;Pesavento et al, 2008;Radford et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The feline calicivirus (FCV) belongs to the family Caliciviridae and is a respiratory pathogen widely prevalent in felines. Cats, tigers, cheetahs and other wild felines are susceptible, kittens aged 6 to 84 days are mainly infected, with a mortality rate of 67% [1,2]. After FCV infection, the animals have oral ulcers, chronic stomatitis, rhinitis, conjunctivitis and pneumonia.…”
Section: Introductionmentioning
confidence: 99%